Soil properties affect the toxicities of 2, 4, 6‐trinitrotoluene (TNT) and hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine (RDX) to the enchytraeid worm Enchytraeus crypticus. (23rd September 2013) - Kuperman, Roman G.; Checkai, Ronald T.; Simini, Michael; Phillips, Carlton T.; Kolakowski, Jan E.; Lanno, Roman
Abstract The authors investigated individual toxicities of 2, 4, 6‐trinitrotoluene (TNT) and hexahydro‐1, 3, 5‐trinitro‐1, 3, 5‐triazine (RDX) to the potworm Enchytraeus crypticus using the enchytraeid reproduction test. Studies were designed to generate ecotoxicological benchmarks that can be used for developing ecological soil‐screening levels for ecological risk assessments of contaminated soils and to identify and characterize the predominant soil physicochemical parameters that can affect the toxicities of TNT and RDX to E. crypticus. Soils, which had a wide range of physicochemical parameters, included Teller sandy loam, Sassafras sandy loam, Richfield clay loam, Kirkland clay loam, and Webster clay loam. Analyses of quantitative relationships between the toxicological benchmarks for TNT and soil property measurements identified soil organic matter content as the dominant property mitigating TNT toxicity for juvenile production by E. crypticus in freshly amended soil. Both the clay and organic matter contents of the soil modulated reproduction toxicity of TNT that was weathered and aged in soil for 3 mo. Toxicity of RDX for E. crypticus was greater in the coarse‐textured sandy loam soils compared with the fine‐textured clay loam soils. The present studies revealed alterations in toxicity to E. crypticus after weathering and aging TNT in soil, and these alterations were soil‐ and endpoint‐specific. Environ Toxicol Chem 2013;32:2648–2659. © 2013 SETAC